A modified colorimetric method of gelatinolytic assay using bacterial collagenase type II as a model - Maslin Osathanunkul (2018)
Coomassie brilliant blue (CBB) heated by microwave was used as a staining dye for measuring gelatinolytic activity. The quantity of gelatin remaining after incubation with bacterial collagenase was determined using the heated CBB, resulting in visible blue pellets. Dimethyl sulfoxide was added to dissolve the dye and measurement of the absorbance at 600 nm was done to detect the level of gelatin (up to 10 μg), with the limit of detection for the amount of collagenase at 50 ng. This approach is rapid, simple, and economic for the purpose of screening for pharmaceutical agents that possess inhibitory activity on collagenase. © 2012 Elsevier Inc. All rights reserved.